1990
DOI: 10.1093/jnci/82.8.697
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Granulocyte-Macrophage Colony-Stimulating Factor in Patients With Advanced Malignancy: A Phase Ib Trial

Abstract: We evaluated the toxic, hematopoietic, and immunomodulatory effects of recombinant human granulocyte-macrophage colony-stimulating factor (rHuGM-CSF). The rHuGM-CSF was administered at doses up to 50 micrograms/kg by daily 2-hour intravenous infusions to 11 patients with advanced malignancy. It induced dose-related increases in cells of the myeloid series, but it had no significant effect on reticulocyte or platelet counts. Bone marrow cellularity increased with higher doses of rHuGM-CSF, but there was a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Kleinerman et al [18] observed no activation of monocyte cytotoxicity after GM-CSF administration nor could Steis et al [36] notice increased production of H202 (measurement of monocyte activation) after stimulation with phorbol myristate acetate. The augmented spontaneous cytotoxicity noticed in the present study is thus probably due to activation of lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Kleinerman et al [18] observed no activation of monocyte cytotoxicity after GM-CSF administration nor could Steis et al [36] notice increased production of H202 (measurement of monocyte activation) after stimulation with phorbol myristate acetate. The augmented spontaneous cytotoxicity noticed in the present study is thus probably due to activation of lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of GM-CSF stems from numerous in vitro and ex vivo studies dating back to the 1980s. These studies demonstrated a complex interplay of mechanisms, including promotion of monocytes to macrophage differentiation, enhanced surface molecule expression and cytotoxic effects (Table II) [45,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Biologic Mechanisms Of Gm-csfmentioning
confidence: 99%
“…Steis et al showed that 1-50 mg/kg recombinant human GM-CSF increased the absolute number of neutrophils, eosinophils, lymphocytes and monocytes in patients with solid tumors [52]. The increase in granulocytic cells (neutrophils and eosinophils) can be associated with anti-viral-and anti-inflammatory-related effects, as well as enhanced phagocytosis.…”
Section: Biologic Mechanisms Of Gm-csfmentioning
confidence: 99%
“…It is also a potent immunostimulator with pleiotropic effects, including the augmentation of Ag presentation in a variety of cells (17)(18)(19)(20)(21)(22), increased expression of MHC class II on monocytes and adhesion molecules on granulocytes and monocytes (23)(24)(25), and amplification of T cell proliferation (26). In animals, the injection of GM-CSF potentiates the protective effects of an antitumor vaccine by enhancing T cell immunity (26), and vaccination with GM-CSF-transduced cells has been shown to be effective in the treatment of experimental tumors in murine models (27)(28)(29)(30).…”
Section: T He Her2/neu Protooncogene (Also Known As C-erbb-2)mentioning
confidence: 99%